Gouverner une AMP, une affaire publique ? Exemples Sud-Méditerranéens - Saïd-Chaouki Chakour; Tarik Dahou (VertigO)
Since the millennium ecosystem assessment, Marine Protected Areas (MPA’s) have become the main instrument of biodiversity conservation in marine environment. However, it is internationally agreed that MPA’s have difficulties to attain their goals. The discrepancies of these areas’ management in southern Mediterranean (Algeria and Tunisia) are described using a perspective of governance analysis. The lack of integration between conservation and sustainable development is mainly due to insufficient studies of local socio-economic dynamics. The governance of MPA’s should increasingly include marine resources’ users.